THE EFFECT OF BLENDED PROBLEM BASED LEARNING AND INDEPENDENCE ON LEARNING OUTCOMES CHEMICAL COURSES - Aisyah; Mustaji; I Wayan Arsana (Institute of Computer Science (IOCS), 2022)
The purpose of this study is to determine the test results: (1) The Effect of Differences in Learning Outcomes between students who study with the Blended-Problem Based Learning model and the Problem Based Learning model in chemistry subjects, (2) Influence between the differences in student learning outcomes who have high and low independence in chemistry subjects, and (3) the interaction between the Blended-Problem Based Learning model and independent learning on the learning outcomes of chemistry subjects. This experimental research was carried out using a 2x2 factorial design. The subjects in this study were students of class X which consisted of four classes with 120 students. The subjects that became the focus of the experiment were taken classically randomly, namely four classes of Mathematics and Natural Sciences1,2,3,4. The research hypothesis was tested using the Analysis of Variant (Anova) statistical test. The results of the calculation show that: (1) There are differences in the effect of the use of the Blended-Problem Based Learning Model and Problem Based Learning Learning Model on students' chemistry learning outcomes, (2) There are differences in the effect of high learning independence and low learning independence on student learning outcomes, and (3) There is an interaction effect between the learning model and independent learning on students' chemistry learning outcomes. Based on the results of the study, it was concluded that using the Blended-Problem Based Learning Model, Problem Based Learning model, and independence could improve students' Chemistry Learning Outcomes.